SISTEM PENUNJANG KEPUTUSAN PEMILIHAN PENGURUS INTI DAN ANGGOTA BARU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS WEBSITE (STUDI KASUS: HIMPUNAN MAHASISWA TEKNIK INFORMATIKA UNIVERSITAS PALANGKA RAYA) - Licantik Licantik; Widiatry Widiatry; Pebriana Lorenza (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2019)
Informatics Engineering of Palangka Raya University have an organization that called Himpunan Mahasiswa Teknik Informatika (HMTI). Problems that are often encountered in a set one of them is in taking the best choice for candidates for core management and membership in each new management period. Another obstacle faced is in making decisions not using methods that can handle these problems with many criteria. The number of considerations certainly has the hope of obtaining good human resources for the set, it's just that sometimes it becomes a difficulty for the old management to take the best choice for the right successor candidate and in accordance with the position and division in the set so that a container is needed to bridge these activities so that they can run well and effectively. The methodology used in the development is by simple additive weighting method and Waterfall According to Sommerville. simple additive weighting method has 4 steps that is determine the criteria, determine the suitability assessment, make a decision matrix based on criteria (Ci) then normalize the matrix, then summarize the multiplication of the R atomized matrix with the increase vector, get the large value chosen as the best (Ai) as a solution.From the test results it can be concluded that the decision support system website for the selection of core managers and new members using the simple additive weighting method at the Collection Informatics Engineering Students of Palangka Raya University is going well